Cemetery Street - Seabrooke, Brenda 1941- (Holiday House, 2008)
Courtney Carmichael, her younger brother, and her depressed, newly-divorced, out-of-work mother move from New Hampshire to Florida into a decrepit house on Cemetery Street, where spooky occurences make the family feel increasingly unsettled.